Totally replaced right hepatic artery in pancreaticoduodenectomy: is this anatomical condition a contraindication to minimally invasive surgery?. Issue 7 (July 2016) - Kim, Ji Hun; Gonzalez-Heredia, Raquel; Daskalaki, Despoina; Rashdan, Mohammad; Masrur, Mario; Giulianotti, Pier C.
Abstract: Background: The appropriate approach, in the case of an aberrant right hepatic artery (RHA) during open pancreaticoduodenectomy (PD), has already been established. The aim of our study is to analyze the short-term surgical and oncological outcomes after robotic PD in patients with anatomical variants, with a special focus on totally replaced RHA. Methods: This study is a retrospective review of a prospectively maintained database collected from consecutive patients who underwent robotic PD at the University of Illinois Hospital and Health Sciences System between September 2007 and April 2015. Results: Fifteen patients (20.5%) presented with an anatomical variation of the RHA. Four patients had an accessory RHA and 11 had a totally replaced RHA. 50% of the cases were recognized by the radiologist preoperatively. There were no significant differences in the pre- and postoperative outcomes of the aberrant and normal RHA group. The mean number of harvested lymph nodes in the totally replaced RHA group was 22.8 ± 11.4. The rate of positive resection margins was 0% in the totally replaced RHA group and 9% in the normal RHA group. Conclusions: This study suggests that robotic PD has no negative impact on surgical and oncological outcomes in patients with a totally replaced RHA.